Variasi Sekuens Gen Mitokondrial Sitokrom C Oksidase I dari Siput Lola (Trochus niloticus) - Agus Nuryanto; Dedy Duryadi Solihin (Fakultas Biologi | Universitas Jenderal Soedirman, 2006)
A study on sequence variation in the mitochondrial DNA of Trochus niloticus has been conducted. Polymerase chain reactions (PCR) technique was applied to amplify cytochrome c oxidase I gene of 533 bp and ABI 310 aotomatic DNA sequencer was used to sequence the PCR product. This study was aimed to know the genetic variation of T. niloticus and the suitability of partial sequence of cytochrome c oxidase I gene as a molecular marker in the genetic study. The results showed that from two T. niloticus specimens, 12 polymorphic sites were detected yielding 2 haplotypes. This indicated a highly genetic variation in thecytochrome c oxidase I (COI) gene of T niloticus. In addition, cytochrome c oxidase I gene was proved to be a suitable marker for the genetics studies of various species of organisms.